Digital Tax Transformation In Indonesia: Evaluating The Impact Of The Coretax System On Taxpayer Compliance - Nabiela Rizki Alifa; Rizwan Ardiansyah (JIM: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to analyze the impact of digital tax transformation through the implementation of the Core Tax Administration System (Coretax) on taxpayer compliance in Indonesia and to identify the supporting and inhibiting factors affecting its effectiveness. The research employs a qualitative descriptive approach using a literature review method based on secondary data from academic journals, government reports, policy documents, and publications from international institutions related to digital tax administration. The findings indicate that Coretax significantly improves administrative efficiency by integrating registration, reporting, payment, and supervision into a single digital platform, thereby simplifying taxpayer interactions, reducing compliance costs, and enhancing transparency and accountability. Empirical evidence shows improvements in formal compliance rates, timeliness of tax reporting, expansion of the taxpayer base, and reductions in tax arrears, while integrated data systems strengthen monitoring and enforcement capabilities and foster voluntary compliance through increased trust in tax authorities. However, the effectiveness of Coretax implementation is constrained by uneven digital infrastructure, cybersecurity risks, limited digital literacy, resistance to organizational change, and regulatory adaptation challenges. In conclusion, Coretax plays a crucial role in improving taxpayer compliance by lowering administrative barriers, strengthening institutional trust, and enhancing enforcement mechanisms, but its long-term success requires sustained investment in infrastructure, capacity building, regulatory support, and public education to ensure that digital transformation leads to durable improvements in tax compliance and revenue performance.